Anti-ultraviolet composite particle, anti-ultraviolet polyamide material and preparation method and application of anti-ultraviolet composite particle and anti-ultraviolet polyamide material
By using composite particles of nano microspheres with core-shell structure and benzotriazole anti-ultraviolet agents in polyamide materials, the problems of stability and UV resistance in high-thermal environments are solved, and the material is realized It has excellent ultraviolet resistance and fiber spinning properties.
Patent Information
- Application Number
- CN202411460529.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
AI Technical Summary
The existing polyamide materials have poor stability in high-thermal environments and have poor UV aging resistance. The uneven dispersion of existing modifiers in the material leads to a decrease in the spunability of fibers.
Nanomicrospheres with core-shell structure and benzotriazole-like anti-UV agents adsorbed outside the nanomicrospheres are zinc oxide and cerium oxide, and the shell is nanoporous silica, which is combined and The porous structure improves UV resistance and adsorbs benzotriazole anti-UV agents outside the shell to enhance migration resistance.
The long-term UV resistance and uniform dispersion of polyamide materials in high-heat environments is achieved, the fibers are spunable, and the material's UV resistance is improved.
Smart Images

Figure CN119286063A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of auxiliary agents, and specifically relates to anti-ultraviolet composite particles, anti-ultraviolet polyamide materials, and preparation methods and applications thereof. Background Art
[0002] Polyamide resin has excellent mechanical properties, chemical resistance, and formability, and is therefore widely used in various parts such as automotive parts, electrical and electronic parts, and industrial machinery parts. However, due to the presence of amide bonds, it has strong water absorption, poor stability in high-temperature environments, and cannot avoid degradation caused by heat and light, which limits its application in certain structural materials.
[0003] At present, the anti-ultraviolet aging of polyamide is mainly carried out through surface coating or polyamide material bulk blending. The former has the advantages of low cost and simple process, but has problems such as unsatisfactory anti-ultraviolet aging performance. Although the latter has good anti-light and heat aging performance, the effect is less durable, and most of the existing modifiers are unevenly dispersed in the polyamide material, which will cause the spinnability of the polyamide fiber to decrease.
[0004] Therefore, developing an anti-ultraviolet composite particle that has excellent and durable anti-ultraviolet aging properties and can be evenly dispersed in a polyamide resin is still a technical problem that urgently needs to be solved in the art. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an anti-ultraviolet composite particle, an anti-ultraviolet polyamide material and a preparation method and application thereof. The anti-ultraviolet composite particles have long-lasting and excellent ultraviolet resistance, and can be evenly dispersed in the polyamide resin without agglomeration, so that the obtained polyamide composite material also has excellent ultraviolet resistance, while not affecting the spinnability of the fiber.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an anti-ultraviolet composite particle, wherein the anti-ultraviolet composite particle comprises nano-microspheres having a core-shell structure and a benzotriazole anti-ultraviolet agent adsorbed outside the nano-microspheres;
[0008] The core of the nano-microsphere with a core-shell structure comprises zinc oxide and cerium oxide, and the shell layer comprises nano-porous silicon dioxide.
[0009] According to research, cerium oxide (CeO 2 ) has a bandgap of 3.1 eV, CeO 2 The particles have a wide absorption band in the range of 300-450nm, and as the particle size decreases, the absorption band redshifts, and has strong ultraviolet light absorption ability.2 After absorbing ultraviolet light, electronic energy level transition will occur and will not induce photocatalysis, which makes it a relatively more ideal spectral inorganic ultraviolet shielding material.
[0010] Based on the above content, the inventors of the present invention creatively discovered during the research process that: cerium oxide and zinc oxide both have good shielding effects on ultraviolet light, and compounding the two can play a synergistic role, and silicon dioxide has no absorption effect itself due to its excessive bandwidth, and only relies on reflection or refraction to reduce the transmittance of ultraviolet light. Therefore, silicon dioxide is coated on the outside of zinc oxide and cerium oxide, and the porosity and nano-spatiality of silicon dioxide are utilized, which can not only effectively maintain the superior ultraviolet resistance of zinc oxide and cerium oxide, but also reduce the direct contact between zinc oxide and cerium oxide and the substrate, effectively weakening the catalytic degradation of the substrate; at the same time, the nanoporous silicon dioxide can also be used as an intermediate, and benzotriazole anti-ultraviolet agents can be uniformly adsorbed on its surface, which can effectively improve the migration resistance of benzotriazole anti-ultraviolet agents, and further improve the ultraviolet resistance of the obtained anti-ultraviolet composite particles, so that it has both long-lasting and excellent ultraviolet resistance.
[0011] Preferably, the D of the nanoparticles having a core-shell structure is 50 The particle size is ≤1.5μm, for example, 1.4μm, 1.3μm, 1.2μm, 1.1μm, 1μm, 0.8μm, 0.6μm, 0.4μm or 0.2μm, etc.
[0012] Preferably, the benzotriazole anti-ultraviolet agent includes any one of 2,2'-methylenebis(4-tert-octyl-6-benzotriazolephenol), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octyloxyphenol or 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol or a combination of at least two thereof.
[0013] Preferably, the molar ratio of the core to the shell is 1:(1-2.5), such as 1:1, 1:1.5, 1:2 or 1:2.5, etc., that is, the molar ratio of the sum of zinc oxide and cerium oxide to silicon dioxide.
[0014] Preferably, the molar ratio of zinc oxide to cerium oxide is 1:(0.33-3), for example, 1:0.33, 1:0.66, 1:1, 1:2 or 1:3.
[0015] Preferably, the zinc oxide and cerium oxide have a D 50 The particle size is ≤100nm, such as 100nm, 90nm, 80nm, 70nm, 60nm, 50nm, 40nm, 30nm, 20nm or 10nm, etc.; select D 50Zinc oxide and cerium oxide with particle sizes both ≤ 100 nm can further improve the anti-ultraviolet performance of the obtained anti-ultraviolet composite particles.
[0016] In a second aspect, the present invention provides a method for preparing anti-ultraviolet composite particles, the preparation method comprising the following steps:
[0017] (1) dispersing zinc oxide, cerium oxide and a surfactant in a solvent A, adding a silicon source to carry out a hydrolysis and polycondensation reaction, and obtaining nano-microspheres with a core-shell structure;
[0018] The benzotriazole anti-ultraviolet agent and the neutralizing agent are mixed in solvent B, and a silane coupling agent is added and heated to obtain a modified anti-ultraviolet agent;
[0019] (2) heating the nano-microspheres obtained in step (1) and the modified anti-ultraviolet agent in solvent C to obtain the anti-ultraviolet composite particles.
[0020] Preferably, the molar ratio of zinc oxide to cerium oxide is 1:(0.33-3), for example, 1:0.33, 1:0.66, 1:1, 1:2 or 1:3.
[0021] Preferably, the surfactant in step (1) comprises polyvinyl pyrrolidone.
[0022] Preferably, based on 1 mol of the zinc oxide in step (1), the amount of the surfactant is 7 to 17 g, for example, 7 g, 8 g, 9 g, 10 g, 12 g, 14 g, 15 g or 17 g.
[0023] Preferably, the solvent A in step (1) comprises ethanol and / or water.
[0024] Preferably, based on the total mass of zinc oxide and cerium oxide in step (1) being 1 g, the volume of solvent A is 19 to 33 mL, for example, 19 mL, 21 mL, 23 mL, 25 mL, 27 mL, 29 mL, 31 mL or 33 mL.
[0025] Preferably, the silicon source in step (1) comprises tetraethyl orthosilicate.
[0026] Preferably, the molar ratio of the sum of zinc oxide and cerium oxide to the silicon source is 1:(1-2.5), for example, 1:1, 1:1.5, 1:2 or 1:2.5.
[0027] Preferably, the pH value of the hydrolysis and polycondensation in step (1) is 7.5 to 9.5, for example, 7.5, 7.7, 7.8, 8, 8.5, 9 or 9.5.
[0028] Preferably, the temperature of the hydrolysis and polycondensation in step (1) is 30-40°C, for example, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C.
[0029] Preferably, the hydrolysis and polycondensation time in step (1) is 5 to 8 hours, for example, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours.
[0030] Preferably, after the hydrolysis and polycondensation in step (1) is completed, the process further includes the steps of centrifugation and drying.
[0031] Preferably, the neutralizing agent in step (1) comprises potassium carbonate and / or potassium hydroxide.
[0032] Preferably, based on 1 mol of the benzotriazole anti-ultraviolet agent in step (1), the amount of the neutralizer is 0.5 to 1 mol, for example, 0.5 mol, 0.55 mol, 0.6 mol, 0.7 mol, 0.8 mol, 0.9 mol or 1 mol.
[0033] Preferably, the solvent B in step (1) comprises N,N-dimethylformamide.
[0034] Preferably, based on the amount of the benzotriazole anti-ultraviolet agent used in step (1) being 1 g, the amount of the solvent B used is 5 to 15 mL, for example, 5 mL, 6 mL, 7 mL, 8 mL, 9 mL, 10 mL, 12 mL, 14 mL or 15 mL.
[0035] Preferably, the silane coupling agent in step (1) includes any one of monochloromethyltriethoxysilane, monochloromethyltrimethoxysilane or 3-chloropropyltrimethoxysilane, or a combination of at least two thereof.
[0036] Preferably, based on 1 mol of the benzotriazole anti-ultraviolet agent in step (1), the amount of the silane coupling agent is 1 to 1.5 mol, such as 1 mol, 1.2 mol, 1.4 mol or 1.5 mol.
[0037] Preferably, the benzotriazole anti-ultraviolet agent in step (1) includes any one of 2,2'-methylenebis(4-tert-octyl-6-benzotriazole phenol), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octyloxyphenol or 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol, or a combination of at least two thereof.
[0038] Preferably, the heating temperature in step (1) is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C.
[0039] Preferably, the heating time in step (1) is 5 to 7 hours, for example, 5 hours, 5.2 hours, 5.5 hours, 6 hours, 6.5 hours or 7 hours.
[0040] Preferably, the heating in step (1) is carried out under stirring conditions.
[0041] Preferably, after the heating in step (1) is completed, the steps of filtering, washing and rotary evaporation to remove the solvent are also included.
[0042] Preferably, the solvent C in step (2) comprises acetone, or a mixture of ethanol and deionized water.
[0043] Preferably, based on the amount of the nanospheres in step (2) being 1 g, the amount of the solvent C is 5 to 15 mL, for example, 5 mL, 6 mL, 7 mL, 8 mL, 9 mL, 10 mL, 11 mL, 12 mL, 13 mL, 14 mL or 15 mL.
[0044] Preferably, the mass ratio of the nanospheres to the modified anti-ultraviolet agent in step (2) is 1:(0.5-2), for example, 1:0.5, 1:0.7, 1:0.9, 1:1.1, 1:1.3, 1:1.5, 1:1.7, 1:1.9 or 1:2, etc.
[0045] Preferably, the heating temperature in step (2) is 50-70°C, for example, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 65°C or 70°C.
[0046] Preferably, the heating time in step (2) is 3 to 6 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0047] Preferably, the heating in step (2) is carried out under stirring conditions.
[0048] Preferably, after the heating in step (2) is completed, the steps of filtering, washing and drying are also included.
[0049] In a third aspect, the present invention provides an anti-UV polyamide material, which includes a polyamide resin and anti-UV composite particles. The anti-UV composite particles are the anti-UV composite particles described in the first aspect, or are the anti-UV composite particles prepared by the preparation method described in the second aspect.
[0050] Preferably, the mass percentage of the anti-UV composite particles in the anti-UV polyamide material is 0.5-3%, for example, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 2%, 2.3%, 2.5%, 2.9% or 3%, etc.
[0051] Preferably, the mass percentage of the polyamide resin in the anti-ultraviolet polyamide material is 97-99.5%, for example, 97%, 97.5%, 98%, 98.5%, 99% or 99.5%.
[0052] Preferably, the polyamide resin includes polyamide 66.
[0053] In a fourth aspect, the present invention provides a method for preparing the UV-resistant polyamide material as described in the third aspect, the preparation method comprising the following steps:
[0054] (A1) mixing a polyamide salt solution and anti-ultraviolet composite particles, and concentrating the mixture by draining water to obtain a polyamide salt concentrate;
[0055] (A2) prepolymerizing, depressurizing and final-polymerizing the polyamide salt concentrate of step (A1) to obtain the UV-resistant polyamide material.
[0056] Preferably, the mass percentage of polyamide salt in the polyamide salt solution of step (A1) is 50-70%, for example, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68% or 70%, etc.
[0057] Preferably, the temperature for concentrating the drainage in step (A1) is 145-165°C, for example, 145°C, 148°C, 150°C, 153°C, 156°C, 159°C, 162°C or 165°C.
[0058] Preferably, the pressure of the drainage concentration in step (A1) is 0.2-0.35 MPa, for example, 0.2 MPa, 0.23 MPa, 0.26 MPa, 0.29 MPa, 0.3 MPa, 0.31 MPa, 0.33 MPa or 0.35 MPa.
[0059] Preferably, the mass percentage of the polyamide salt in the polyamide salt concentrate in step (A1) is 70-85%, for example, 70%, 73%, 75%, 77%, 79%, 81%, 83% or 85%.
[0060] Preferably, the prepolymerization temperature in step (A2) is 245-265°C, for example, 245°C, 247°C, 249°C, 251°C, 253°C, 255°C, 257°C, 259°C, 261°C, 263°C or 265°C, etc.
[0061] Preferably, the prepolymerization time in step (A2) is 1 to 2 h, for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h.
[0062] Preferably, the prepolymerization pressure in step (A2) is 1.7-1.9 MPa, for example, 1.7 MPa, 1.72 MPa, 1.75 MPa, 1.8 MPa, 1.82 MPa, 1.85 MPa or 1.9 MPa.
[0063] Preferably, the pressure after decompression in step (A2) is 0 to 0.02 MPa, such as 0 MPa, 0.005 MPa, 0.01 MPa, 0.015 MPa or 0.02 MPa.
[0064] Preferably, the temperature of the final polymerization in step (A2) is 270-290°C, for example, 270°C, 275°C, 280°C, 285°C or 290°C.
[0065] Preferably, the final polymerization time in step (A2) is 200 to 1000 s, for example, 200 s, 300 s, 400 s, 500 s, 600 s, 700 s, 800 s, 900 s or 1000 s.
[0066] Preferably, the pressure of the final polymerization in step (A2) is -0.1 to 0 MPa, for example, -0.1 MPa, -0.09 MPa, -0.08 MPa, -0.06 MPa, -0.04 MPa, -0.02 MPa or 0 MPa.
[0067] Compared with the prior art, the present invention has the following beneficial effects:
[0068] The anti-ultraviolet composite particles provided by the present invention include nano-microspheres with a core-shell structure and a benzotriazole anti-ultraviolet agent adsorbed outside the nano-microspheres, wherein the core of the nano-microspheres includes zinc oxide and cerium oxide, and the shell layer includes silicon dioxide; by selecting zinc oxide and cerium oxide as the core, silicon dioxide as the shell layer, and adsorbing the benzotriazole anti-ultraviolet agent outside the shell layer, the obtained anti-ultraviolet composite particles have both long-lasting and excellent anti-ultraviolet properties, and can be evenly dispersed in a polyamide resin, so that the obtained polyamide material also has excellent anti-ultraviolet properties, and at the same time does not affect the spinnability of the polyamide fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 A schematic diagram of the cross-sectional structure of the anti-ultraviolet composite particles provided by the present invention;
[0070] Among them, 1-nano microspheres with core-shell structure, 2-benzotriazole anti-ultraviolet agent, 1-1-core, 1-2-shell. DETAILED DESCRIPTION
[0071] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0072] Example 1
[0073] An anti-ultraviolet composite particle, the cross-sectional structure diagram of which is as follows Figure 1 As shown, it includes a nano-microsphere 1 with a core-shell structure and a benzotriazole anti-ultraviolet agent 2 adsorbed on the outside of the nano-microsphere 1;
[0074] Among them, the D of nanoparticles 1 with core-shell structure 50 The particle size is 1 μm, including a core 1-1 and a shell 1-2;
[0075] Core 1-1 includes nano zinc oxide (D 50 Particle size 50nm) and nano cerium oxide (D 50 The particle size is 60nm), and the shell 1-2 is silicon dioxide;
[0076] Benzotriazole anti-ultraviolet agent 2 is 2,2'-methylenebis(4-tert-octyl-6-benzotriazolephenol) (UV-360);
[0077] The preparation method of the anti-ultraviolet composite particles provided in this embodiment comprises the following steps:
[0078] (1) adding nano zinc oxide and nano cerium oxide in a molar ratio of 1:1.85 to an anhydrous ethanol solution containing 10 g / L polyvinyl pyrrolidone (PVP) to obtain a pre-dispersion, wherein the total concentration of nano zinc oxide and nano cerium oxide in the pre-dispersion is 0.04 g / mL;
[0079] Under the condition of electric stirring and ultrasonic assistance, tetraethyl orthosilicate is added to the obtained pre-dispersion as a silicon source, and the molar ratio of the sum of nano zinc oxide and nano cerium oxide to tetraethyl orthosilicate is controlled to be 1:1 to form a mixed solution, and then ammonia water is added to adjust the pH value of the system to 7.5, and hydrolyze and condense at 40°C for 6 hours to form silicon dioxide, and then centrifugally washed and dried to obtain nano-microspheres with a core-shell structure;
[0080] UV-360 and K in a molar ratio of 1:0.5 2 CO 3 Mixing in N,N-dimethylformamide to make the concentration of UV-360 in the mixed solution 0.1 g / mL, then adding monochloromethyltrimethoxysilane in a molar ratio of 1:1 to UV-360, reacting at 60° C. for 6 hours, and filtering, washing, and removing the solvent by rotary evaporation to obtain a modified anti-ultraviolet agent;
[0081] (2) Mixing the nanoparticles with a core-shell structure obtained in step (1) in a mass ratio of 1:1.3 and the modified anti-ultraviolet agent in a mixture of ethanol and deionized water in a volume ratio of 1:1, wherein the concentration of the nanoparticles in the mixture is 0.1 g / mL, stirring and mixing at 60° C. for 4 h, and filtering, washing, and drying to obtain the anti-ultraviolet composite particles.
[0082] Example 2
[0083] An anti-ultraviolet composite particle, the structure of which is the same as that of Example 1, comprising nano-microspheres with a core-shell structure and a benzotriazole anti-ultraviolet agent adsorbed on the outside of the nano-microspheres;
[0084] Among them, the D 50 The particle size is 1.3 μm, including the core and shell;
[0085] The core includes nano zinc oxide (D 50 Particle size 80nm) and nano cerium oxide (D 50 The particle size is 70nm), and the shell is silicon dioxide;
[0086] The benzotriazole anti-ultraviolet agent is 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octoxyphenol (UV-1164);
[0087] The preparation method of the anti-ultraviolet composite particles provided in this embodiment comprises the following steps:
[0088] (1) adding nano zinc oxide and nano cerium oxide in a molar ratio of 1:2 to an anhydrous ethanol solution containing 10 g / L polyvinyl pyrrolidone (PVP) to obtain a pre-dispersion, wherein the total concentration of nano zinc oxide and nano cerium oxide in the pre-dispersion is 0.04 g / mL;
[0089] Under the condition of electric stirring and ultrasonic assistance, tetraethyl orthosilicate is added to the obtained pre-dispersion as a silicon source, and the molar ratio of the sum of nano zinc oxide and nano cerium oxide to tetraethyl orthosilicate is controlled to be 1:1 to form a mixed solution, and then ammonia water is added to adjust the pH value of the system to 8, and hydrolyze and condense at 40°C for 5h to form silicon dioxide, and then centrifugally washed and dried to obtain nano-microspheres with a core-shell structure;
[0090] UV-1164 and K in a molar ratio of 1:0.5 2 CO 3 Mixing in N,N-dimethylformamide to make the concentration of UV-1164 in the mixed solution 0.1 g / mL, then adding 3-chloropropyltrimethoxysilane in a molar ratio of 1:1.2 to UV-1164, reacting at 60° C. for 6 hours, and filtering, washing, and removing the solvent by rotary evaporation to obtain a modified anti-ultraviolet agent;
[0091] (2) The nanoparticles with a core-shell structure obtained in step (1) and the modified anti-ultraviolet agent in a mass ratio of 1:0.8 are heated and mixed in a mixture of ethanol and deionized water in a volume ratio of 1:1, wherein the concentration of the nanoparticles in the mixture is 0.1 g / mL, and the mixture is stirred, heated and mixed at 60° C. for 4 h, and the volatile components are removed by filtration, washing, drying and vacuuming to obtain the anti-ultraviolet composite particles.
[0092] Example 3
[0093] An anti-ultraviolet composite particle, the structure of which is the same as that of Example 1, comprising nano-microspheres with a core-shell structure and a benzotriazole anti-ultraviolet agent adsorbed on the outside of the nano-microspheres;
[0094] Among them, the D 50 The particle size is 0.8 μm, including the core and shell;
[0095] The core includes nano zinc oxide (D 50 Particle size 30nm) and nano cerium oxide (D 50 The particle size is 40nm), and the shell is silicon dioxide;
[0096] The benzotriazole anti-ultraviolet agent is 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octoxyphenol (UV-1577);
[0097] The preparation method of the anti-ultraviolet composite particles provided in this embodiment comprises the following steps:
[0098] (1) adding nano zinc oxide and nano cerium oxide in a molar ratio of 1:1.5 to an anhydrous ethanol solution containing 10 g / L polyvinyl pyrrolidone (PVP) to obtain a pre-dispersion, wherein the total concentration of nano zinc oxide and nano cerium oxide in the pre-dispersion is 0.04 g / mL;
[0099] Under the condition of electric stirring and ultrasonic assistance, tetraethyl orthosilicate is added to the obtained pre-dispersion as a silicon source, and the molar ratio of the sum of nano zinc oxide and nano cerium oxide to tetraethyl orthosilicate is controlled to be 1:1 to form a mixed solution, and then ammonia water is added to adjust the pH value of the system to 8.5, and hydrolyze and condense at 40°C for 5h to form silicon dioxide, and then centrifugally washed and dried to obtain nano-microspheres with a core-shell structure;
[0100] UV-1577 and K in a molar ratio of 1:1 2 CO 3Mixing in N,N-dimethylformamide to make the concentration of UV-1577 in the mixed solution 0.1 g / mL, then adding 3-chloropropyltrimethoxysilane in a molar ratio of 1:1.2 to UV-1577, reacting at 60° C. for 6 hours, and filtering, washing, and removing the solvent by rotary evaporation to obtain a modified anti-ultraviolet agent;
[0101] (2) The nanoparticles with a core-shell structure obtained in step (1) and the modified anti-ultraviolet agent in a mass ratio of 1:1.8 are heated and mixed in a mixture of ethanol and deionized water in a volume ratio of 1:1, wherein the concentration of the nanoparticles in the mixture is 0.1 g / mL, and the mixture is stirred, heated and mixed at 60° C. for 4 h, and the volatile components are removed by filtration, washing, drying and vacuuming to obtain the anti-ultraviolet composite particles.
[0102] Embodiments 4 to 7
[0103] An anti-ultraviolet composite particle, which differs from Example 1 in that, in step (2) of the preparation method, the mass ratios of the nano-microspheres with a core-shell structure to UV-360 are 1:0.5 (Example 4), 1:2 (Example 5), 1:0.4 (Example 6) and 1:2.5 (Example 7), respectively, and the other structures, materials, parameters and preparation methods are the same as those in Example 1.
[0104] Embodiments 8 to 10
[0105] An anti-ultraviolet composite particle, which differs from Example 1 in that, in step (1) of the preparation method, the molar ratio of nano zinc oxide to nano cerium oxide is 1:1 (Example 8), 1:0.25 (Example 9) and 1:4 (Example 10), respectively, and the other structures, materials, parameters and preparation methods are the same as those in Example 1.
[0106] Examples 11 to 13
[0107] An anti-ultraviolet composite particle, which differs from Example 1 in that, in step (1) of the preparation method, the ratio of the sum of nano zinc oxide and nano cerium oxide to tetraethyl orthosilicate is 1:1.7 (Example 11), 1:0.7 (Example 12) and 1:3 (Example 13), respectively, and the other structures, materials, parameters and preparation methods are the same as those in Example 1.
[0108] Embodiment 14
[0109] An anti-ultraviolet composite particle, which is different from Example 1 in that the nano-microsphere 1 having a core-shell structure has a D 50 The particle size is 2.2 μm, and other structures, materials, parameters and preparation methods are the same as those in Example 1.
[0110] Comparative Example 1
[0111] An anti-ultraviolet composite particle, the structure of which is the same as that of Example 1, comprising nano-microspheres with a core-shell structure and a benzotriazole anti-ultraviolet agent adsorbed on the outside of the nano-microspheres;
[0112] Among them, the D 50 The particle size is 1 μm, including the core and shell;
[0113] The core is nano zinc oxide (D 50 The particle size is 50nm), and the shell is silicon dioxide;
[0114] The benzotriazole anti-ultraviolet agent is 2,2'-methylenebis(4-tert-octyl-6-benzotriazolephenol) (UV-360);
[0115] The preparation method of the anti-ultraviolet composite particles provided in this comparative example comprises the following steps:
[0116] (1) adding nano zinc oxide to an anhydrous ethanol solution containing 10 g / L polyvinyl pyrrolidone (PVP) to obtain a pre-dispersion, wherein the total concentration of nano zinc oxide in the pre-dispersion is 0.04 g / mL;
[0117] Under the conditions of electric stirring and ultrasonic assistance, tetraethyl orthosilicate is added to the obtained pre-dispersion as a silicon source, and the molar ratio of nano zinc oxide to tetraethyl orthosilicate is controlled to be 1:1 to form a mixed solution, and then ammonia water is added to adjust the pH value of the system to 7.5, and hydrolyze and condense at 40°C for 6 hours to form silicon dioxide, and then centrifugally washed and dried to obtain nano-microspheres with a core-shell structure;
[0118] UV-360 and K in a molar ratio of 1:0.5 2 CO 3 Mixing in N,N-dimethylformamide to make the concentration of UV-360 in the mixed solution 0.1 g / mL, then adding monochloromethyltrimethoxysilane in a molar ratio of 1:1 to UV-360, reacting at 60° C. for 6 hours, and filtering, washing, and removing the solvent by rotary evaporation to obtain a modified anti-ultraviolet agent;
[0119] (2) Mixing the nanoparticles with a core-shell structure obtained in step (1) in a mass ratio of 1:1.3 and the modified anti-ultraviolet agent in a mixture of ethanol and deionized water in a volume ratio of 1:1, wherein the concentration of the nanoparticles in the mixture is 0.1 g / mL, stirring and mixing at 60° C. for 4 h, and filtering, washing, and drying to obtain the anti-ultraviolet composite particles.
[0120] Comparative Example 2
[0121] An anti-ultraviolet composite particle, the structure of which is the same as that of Example 1, comprising nano-microspheres with a core-shell structure and a benzotriazole anti-ultraviolet agent adsorbed on the outside of the nano-microspheres;
[0122] Among them, the D 50 The particle size is 1 μm, including the core and shell;
[0123] The core is nano-cerium oxide (D 50 The particle size is 60nm), and the shell is silicon dioxide;
[0124] The benzotriazole anti-ultraviolet agent is 2,2'-methylenebis(4-tert-octyl-6-benzotriazolephenol) (UV-360);
[0125] The preparation method of the anti-ultraviolet composite particles provided in this comparative example comprises the following steps:
[0126] (1) adding nano-cerium oxide to an anhydrous ethanol solution containing 10 g / L polyvinyl pyrrolidone (PVP) to obtain a pre-dispersion, wherein the total concentration of nano-cerium oxide in the pre-dispersion is 0.04 g / mL;
[0127] Under conditions of electric stirring and ultrasonic assistance, tetraethyl orthosilicate is added to the obtained pre-dispersion as a silicon source, and the molar ratio of the total amount of nano-cerium oxide to tetraethyl orthosilicate is controlled to be 1:1 to form a mixed solution, and then ammonia water is added to adjust the pH value of the system to 7.5, and hydrolyze and condense at 40°C for 6 hours to form silicon dioxide, and then centrifugally washed and dried to obtain nano-microspheres with a core-shell structure;
[0128] UV-360 and K in a molar ratio of 1:0.5 2 CO 3 Mixing in N,N-dimethylformamide to make the concentration of UV-360 in the mixed solution 0.1 g / mL, then adding monochloromethyltrimethoxysilane in a molar ratio of 1:1 to UV-360, reacting at 60° C. for 6 hours, and filtering, washing, and removing the solvent by rotary evaporation to obtain a modified anti-ultraviolet agent;
[0129] (2) Mixing the nanoparticles with a core-shell structure obtained in step (1) in a mass ratio of 1:1.3 and the modified anti-ultraviolet agent in a mixture of ethanol and deionized water in a volume ratio of 1:1, wherein the concentration of the nanoparticles in the mixture is 0.1 g / mL, stirring and mixing at 60° C. for 4 h, and filtering, washing, and drying to obtain the anti-ultraviolet composite particles.
[0130] Comparative Example 3
[0131] A kind of anti-ultraviolet composite particle, D 50 The particle size is 1 μm and has a core-shell structure, including a core and a shell;
[0132] Among them, the core includes nano zinc oxide (D 50 Particle size 50nm) and nano cerium oxide (D50 The particle size is 60nm), and the shell is silicon dioxide;
[0133] The preparation method of the anti-ultraviolet composite particles provided in this comparative example comprises the following steps:
[0134] (1) adding nano zinc oxide and nano cerium oxide in a molar ratio of 1:1.85 to an anhydrous ethanol solution containing 10 g / L polyvinyl pyrrolidone (PVP) to obtain a pre-dispersion, wherein the total concentration of nano zinc oxide and nano cerium oxide in the pre-dispersion is 0.04 g / mL;
[0135] (2) Under conditions of electric stirring and ultrasonic assistance, tetraethyl orthosilicate is added to the obtained pre-dispersion as a silicon source, and the molar ratio of the sum of nano-zinc oxide and nano-cerium oxide to tetraethyl orthosilicate is controlled to be 1:1 to form a mixed solution, and then ammonia water is added to adjust the pH value of the system to 7.5, and hydrolysis and condensation are carried out at 40°C for 6 hours to form silicon dioxide, and then centrifugal washing and drying are carried out to obtain nano-microspheres with a core-shell structure, namely, anti-ultraviolet composite particles.
[0136] Comparative Example 4
[0137] The invention discloses an anti-ultraviolet composite particle, and the preparation method thereof comprises: mixing nano zinc oxide and nano cerium oxide in a molar ratio of 1:1.85, and then adding silicon dioxide for mixing, wherein the molar ratio of the sum of the nano zinc oxide and the nano cerium oxide to the silicon dioxide is 1:1, to obtain the anti-ultraviolet composite particle.
[0138] Application Example 1
[0139] An anti-ultraviolet polyamide material, comprising 98 parts by weight of polyamide 66 and 2 parts by weight of anti-ultraviolet composite particles (Example 1);
[0140] The preparation method of the UV-resistant polyamide material provided in this application example comprises the following steps:
[0141] (1) adding adipic acid and hexamethylenediamine in a molar ratio of 1:1 into water in sequence to form a salt, thereby obtaining a polyamide salt solution having a mass percentage content of 60%;
[0142] (2) mixing the polyamide salt solution obtained in step (1) and the anti-ultraviolet composite particles provided in Example 1, draining and concentrating at 158° C. and 0.29 MPa to obtain a polyamide salt concentrate having a mass percentage of 81%;
[0143] (3) The polyamide salt concentrated solution obtained in step (2) is heated, pre-polymerized at 255° C. and 1.80 MPa for 1.5 h, then depressurized to 0.01 MPa, and finally final-polymerized at 280° C. and −0.1 MPa for 500 s to obtain the UV-resistant polyamide material.
[0144] Application Examples 2 to 14 and Comparative Application Examples 1 to 4
[0145] An anti-ultraviolet polyamide material is different from Application Example 1 in that the anti-ultraviolet composite particles provided in Examples 2 to 14 and Comparative Examples 1 to 4 are used to replace the anti-ultraviolet composite particles provided in Example 1, and other substances, dosages and preparation methods are the same as those in Application Example 1.
[0146] Performance Testing:
[0147] (1) Anti-ultraviolet performance: refer to the test method provided in GB / T 18830-2009 "Evaluation of UV protection performance of textiles" to test UVA transmittance and UVA transmittance after 100 hours of ultraviolet irradiation; the ultraviolet irradiation process is carried out in a UV aging box.
[0148] (2) Spinnability: The prepared UV-resistant polyamide material is melt-spun, and a comprehensive evaluation is made on the smoothness of the spinning process, the severity of the hanging phenomenon, the number of broken fibers, the surface smoothness of the fiber, etc. If the spinning process is smooth, the hanging phenomenon is slight, there is no broken fiber, and the surface of the spun fiber is smooth, the spinnability is excellent, otherwise it is poor.
[0149] According to the above test method, the UV-resistant polyamide materials provided by Examples 1 to 14 and Comparative Application Examples 1 to 4 were tested, and the test results are shown in Table 1:
[0150] Table 1
[0151]
[0152] Note: “—” means the test cannot be performed.
[0153] From the data in Table 1, we can see that:
[0154] The present invention introduces specific anti-ultraviolet composite particles to make the obtained anti-ultraviolet polyamide material have better anti-ultraviolet performance and good spinnability; in particular, the initial UVA transmittance of the anti-ultraviolet polyamide material provided by Application Examples 1 to 5, Application Example 8 and Application Example 11 is 1.12-1.92%, and the UVA transmittance after 100 hours of ultraviolet irradiation is 1.38-1.96%, which has the most excellent anti-ultraviolet performance and excellent spinnability.
[0155] Among them, from the comparison between Application Example 1 and Application Examples 6 to 7, it can be seen that a slightly lower or higher content of benzotriazole anti-ultraviolet agent in the anti-ultraviolet composite particles will lead to a higher UVA transmittance of the obtained anti-ultraviolet polyamide material both initially and after 100 hours of ultraviolet irradiation, and a decrease in anti-ultraviolet performance.
[0156] From the comparison between Application Example 1 and Application Examples 9-10, it can be seen that a slightly lower or higher content of nano-cerium oxide in the anti-ultraviolet composite particles will also lead to a higher UVA transmittance of the obtained anti-ultraviolet polyamide material at the beginning and after 100 hours of ultraviolet irradiation, and a decrease in the anti-ultraviolet performance.
[0157] From the comparison between Application Example 1 and Application Example 12, it can be seen that a slightly lower content of silicon dioxide (silicon source) in the anti-ultraviolet composite particles will result in a higher UVA transmittance of the obtained anti-ultraviolet polyamide material after 100 hours of ultraviolet irradiation.
[0158] From the comparison between Application Example 1 and Application Example 13, it can be seen that a slightly higher content of silicon dioxide (silicon source) in the anti-ultraviolet composite particles will also lead to higher UVA transmittance of the obtained anti-ultraviolet polyamide material initially and after 100 hours of ultraviolet irradiation.
[0159] However, from the comparison between Application Example 1 and Application Example 14, it can be seen that if the particle size of the anti-ultraviolet composite particles is too large, the spinnability of the obtained anti-ultraviolet polyamide material will be poor, and it will be difficult to spin to obtain fiber products.
[0160] Further, from the comparison between Application Example 1 and Comparative Application Examples 1 to 3, it can be seen that the absence of nano cerium oxide in the anti-UV composite particles (Comparative Example 1), the absence of nano zinc oxide in the anti-UV composite particles (Comparative Example 2), and the absence of benzotriazole anti-UV agents in the anti-UV composite particles (Comparative Example 3) will all lead to the obtained anti-UV polyamide material having too high initial UVA transmittance and after 100 hours of UV irradiation, and having almost no anti-UV performance.
[0161] From the comparison between Application Example 1 and Comparative Application Example 4, it can be seen that if the anti-UV composite particles are only mixed by physical blending and then the polyamide resin is introduced, the spinnability of the resulting anti-UV polyamide material will be average, and the UVA transmittance of the textiles initially and after 100 hours of ultraviolet irradiation will be extremely high, and they will not have UV resistance.
[0162] The applicant declares that the present invention illustrates an anti-ultraviolet composite particle, an anti-ultraviolet polyamide material, and a preparation method and application thereof through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An anti-ultraviolet composite particle, characterized in that: The anti-ultraviolet composite particles include nano-microspheres with a core-shell structure and a benzotriazole anti-ultraviolet agent adsorbed outside the nano-microspheres; The core of the nano-microsphere with a core-shell structure comprises zinc oxide and cerium oxide, and the shell comprises silicon dioxide.
2. The anti-ultraviolet composite particles according to claim 1, characterized in that: The nano-microspheres with core-shell structure have 50 Particle size ≤1.5μm; Preferably, the mass ratio of the nano-microspheres with core-shell structure to the benzotriazole anti-ultraviolet agent is 1:(0.5-2); Preferably, the benzotriazole anti-ultraviolet agent includes any one of 2,2'-methylenebis(4-tert-octyl-6-benzotriazolephenol), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octyloxyphenol or 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol or a combination of at least two thereof.
3. The anti-ultraviolet composite particles according to claim 1 or 2, characterized in that: The molar ratio of the core to the shell is 1:(1-2.5); Preferably, the molar ratio of zinc oxide to cerium oxide is 1:(0.33-3); Preferably, the D of the zinc oxide and the cerium oxide 50 The particle size is ≤100nm.
4. A method for preparing anti-ultraviolet composite particles, characterized in that: The preparation method comprises the following steps: (1) dispersing zinc oxide, cerium oxide and a surfactant in a solvent A, adding a silicon source to carry out a hydrolysis and polycondensation reaction, and obtaining nano-microspheres with a core-shell structure; The benzotriazole anti-ultraviolet agent and the neutralizing agent are mixed in solvent B, and a silane coupling agent is added and heated to obtain a modified anti-ultraviolet agent; (2) The nano-microspheres with a core-shell structure obtained in step (1) and the modified anti-ultraviolet agent are heated in a solvent C to obtain the anti-ultraviolet composite particles.
5. The preparation method according to claim 4, characterized in that: The molar ratio of zinc oxide to cerium oxide in step (1) is 1:(0.33-3); Preferably, the surfactant comprises polyvinyl pyrrolidone; Preferably, based on the amount of solvent A used in step (1) being 1 L, the amount of surfactant used is 7 to 17 g; Preferably, the solvent A in step (1) comprises ethanol and / or water; Preferably, based on the total mass of the zinc oxide and cerium oxide in step (1) being 1 g, the volume of the solvent A is 19 to 33 mL; Preferably, the silicon source in step (1) comprises tetraethyl orthosilicate; Preferably, the molar ratio of the sum of zinc oxide and cerium oxide to the silicon source in step (1) is 1:(1-2.5); Preferably, the pH value of the hydrolysis and polycondensation in step (1) is 7.5 to 9.5; Preferably, the temperature of the hydrolysis and polycondensation in step (1) is 30 to 40° C. and the time is 5 to 8 hours; Preferably, after the hydrolysis and polycondensation in step (1) is completed, the process further includes the steps of centrifugation and drying.
6. The preparation method according to claim 4 or 5, characterized in that: The neutralizing agent in step (1) includes potassium carbonate and / or potassium hydroxide; Preferably, based on the amount of the benzotriazole anti-ultraviolet agent used in step (1) being 1 mol, the amount of the neutralizing agent used is 0.5 to 1 mol; Preferably, the solvent B in step (1) comprises N,N-dimethylformamide; Preferably, based on the amount of the benzotriazole anti-ultraviolet agent used in step (1) being 1 g, the amount of the solvent B used is 5 to 15 mL; Preferably, the benzotriazole anti-ultraviolet agent in step (1) includes any one of 2,2'-methylenebis(4-tert-octyl-6-benzotriazole phenol), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octyloxyphenol or 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol or a combination of at least two thereof; Preferably, the silane coupling agent in step (1) includes any one of monochloromethyltriethoxysilane, monochloromethyltrimethoxysilane or 3-chloropropyltrimethoxysilane, or a combination of at least two thereof; Preferably, based on the amount of the benzotriazole anti-ultraviolet agent used in step (1) being 1 mol, the amount of the silane coupling agent used is 1.0 to 1.5 mol; Preferably, the heating temperature in step (1) is 50-70° C. and the heating time is 5-7 h; Preferably, the heating in step (1) is carried out under stirring; Preferably, after the heating in step (1) is completed, the steps of filtering, washing and removing the solvent by rotary evaporation are also included.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The solvent C in step (2) comprises acetone, or a mixture of ethanol and deionized water; Preferably, based on the amount of the nanospheres used in step (2) being 1 g, the amount of the solvent C used is 5 to 15 mL; Preferably, the mass ratio of the nano-microspheres to the modified anti-ultraviolet agent in step (2) is 1:(0.5-2); Preferably, the heating temperature in step (2) is 50-70° C. and the heating time is 3-6 hours; Preferably, the heating in step (2) is carried out under stirring; Preferably, after the heating in step (2) is completed, the steps of filtering, washing and drying are also included.
8. An anti-ultraviolet polyamide material, characterized in that: The anti-ultraviolet polyamide material comprises polyamide resin and anti-ultraviolet composite particles; The anti-ultraviolet composite particles are the anti-ultraviolet composite particles as described in any one of claims 1 to 4, or the anti-ultraviolet composite particles prepared by the preparation method as described in any one of claims 5 to 7.
9. The UV-resistant polyamide material according to claim 8, characterized in that: The mass percentage of the anti-ultraviolet composite particles in the anti-ultraviolet polyamide material is 0.5-3%; Preferably, the mass percentage of the polyamide resin in the anti-ultraviolet polyamide material is 97-99.5%; Preferably, the polyamide resin includes polyamide 66.
10. A method for preparing the UV-resistant polyamide material according to claim 8 or 9, characterized in that: The preparation method comprises the following steps: (A1) mixing a polyamide salt solution and anti-ultraviolet composite particles, and concentrating the mixture by draining water to obtain a polyamide salt concentrate; (A2) prepolymerizing, depressurizing and final-polymerizing the polyamide salt concentrate of step (A1) to obtain the UV-resistant polyamide material; Preferably, the mass percentage of the polyamide salt in the polyamide salt solution in step (A1) is 50-70%; Preferably, the temperature of the wastewater concentration in step (A1) is 145-165°C; Preferably, the pressure of the drainage concentration in step (A1) is 0.2-0.35 MPa; Preferably, the mass percentage of the polyamide salt in the polyamide salt concentrate in step (A1) is 70-85%; Preferably, the prepolymerization temperature in step (A2) is 245-265° C. and the time is 1-2 h; Preferably, the prepolymerization pressure in step (A2) is 1.7 to 1.9 MPa; Preferably, the pressure after decompression in step (A2) is 0 to 0.02 MPa; Preferably, the temperature of the final polymerization in step (A2) is 270-290° C. and the time is 200-1000 s; Preferably, the pressure of the final polymerization in step (A2) is -0.1 to 0 MPa.
Citation Information
Cited By
Preparation method of anti-cracking modified EVA cable material
CN119798830A
A preparation method of crack-resistant modified EVA cable material
CN119798830B
Preparation method of uvioresistant modified starch-based composite material and application of uvioresistant modified starch-based composite material in pesticide
CN121774033A
